2017
DOI: 10.1111/1477-9552.12231
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Long‐run Technical Efficiency of German Dairy Farms: A Bayesian Approach*

Abstract: In parametric efficiency studies, two alternative approaches exist to provide an estimate of the long-run efficiency of firms: the dynamic stochastic frontier model and the generalised true random-effects model. We extend the former in order to allow for heterogeneity in the long-run technical efficiency of firms. This model is based on potential differences in firm-specific characteristics and in firms' inefficiency persistence. The model is applied to an unbalanced micro-panel of German dairy farms over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Furthermore, Skevas et al . (2018a) use a reduced form dynamic inefficiency model and report an average dynamic inefficiency score of 35% for German dairy farms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Skevas et al . (2018a) use a reduced form dynamic inefficiency model and report an average dynamic inefficiency score of 35% for German dairy farms.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the goal of profit maximization can be achieved by minimizing the cost of producing a fixed (quota) output. According to Skevas et al (2018), output can be assumed exogenous under this optimization condition.…”
Section: Methodsmentioning
confidence: 99%
“…The current studies focusing on milk productivity in EU countries have provided different results for some aspects of the dairy sector and the same results for other aspects of milk production. Skevas et al (2018) showed that technical efficiency at German dairy producers has declined over time and the change in productivity has been driven by technological change. By contrast, Lansink et al (2015) and Dakpo et al (2019) concluded that the productivity of Dutch and French dairy farms has increased as a result of improvements in technical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the goal of profit maximization can be achieved by minimizing the cost of producing a fixed (quota) output. According to Skevas et al (2018), the outputs can be assumed as exogenous under this optimization condition.…”
Section: Methodsmentioning
confidence: 99%